THE IMPACT OF THE PANDEMIC CAUSED BY COVID-19 ON THE EPIDEMIOLOGICAL STATE OF HIV INFECTION IN UKRAINE - Mykola D. Chemych; Dmytro S. Sosnovenko; Zoryana V. Kobliuk; Nataliia V. Skrypka (Східноукраїнський медичний журнал, 2022)
HIV infection is a human disease with progressive dysfunction of the body's immune system and a long asymptomatic course.